Evaluation of phytochemical composition, antioxidant and anti- diabetic activities of Mitragyna speciosa Methanolic Extract (MSME) - Zailan, Nur Fatin Zalikha; Sarchio, Seri Narti Edayu; Hassan, Masriana (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: The therapeutic potential of plant-based or herbal medicine has been widely embraced by the public as a prevention and remedy for many illnesses. Mitragyna speciosa is one of the medicinal plant that exhibit the opioid-like effects of analgesia. This study aimed to evaluate the phytochemical content, antioxidant activity, and alpha-amylase enzyme inhibition of Mitragyna speciosa methanolic extract (MSME). Methods: The phytochemical composition of MSME was analyzed for secondary metabolites using UHPLC-TWIMS-QTOF-MS/MS. The total phe- nolic content (TPC), total flavonoid content (TFC), antioxidant scavenging activities (2,2-diphenyl-1-picrylhydrazyl [DPPH] and 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) [ABTS] assays) and α-amylase enzyme inhi- bition activities of MSME were analyzed in comparison to positive control Pterostilbene and acarbose, respectively. Results: Analysis of UHPLC-TWIMS-QTOF-MS/MS has characterized the presence of at least five different bioactive compounds, mostly derivatives of flavonoids and polyphenols. A significantly higher level of TFC (347.72±15.97 mg QE/g extract; p = 0.0005), but a significantly lower level of TPC (167.43±13.50 mg GAE/g extract; p = 0.002) was detected in MSME (1 mg/mL) compared to Pterostilbene. MSME presented antioxidant activity which has no significant difference compared to Pterostilbene as determined by DPPH (MSME IC50 = 4.34±1.79 µg/mL; p = 0.727) and ABTS (MSME IC50 = 4.25±1.59 µg/mL; p = 0.311) assays. Moreover, MSME also exhibited anti-diabetic effects through inhibition of α-amylase activity (IC50 = 0.01±7.18 mg/mL) which shows a significant difference (p = 0.009) compared to acarbose. Conclusion: This finding suggests that MSME has bioactive phytochemicals and exhibits po- tential antioxidant and anti-diabetic properties.